Cacao (Theobroma cacao L.) seedlings growth in different pot sizes - Osorio G., Mónica Andrea; Leiva R., Edna Ivonne; Ramírez P., Ramiro (Revista de Ciencias Agrícolas, 2017)
Pot volume is a key factor for the propagation of cacao, since the pot size influences growth and development of seedlings which are crucial factors for crop establishment. In this work, the effect of different pot sizes 0.01; 0.02 y 0.1m3 (substrate volume) and nursery duration on cocoa growth were compared, and changes in the substrate-confined were also evaluated. Seeds of cocoa were sowed in different pot sizes: 25, 45 and 70cm. Leaf temperatures was measured and seedlings were collected to quantify partitioned biomass and taproot growth. Penetration resistance, temperature, humidity and porosity of the substrate were evaluated at the same time. The results evidenced significant differences (P <0.05) in total phytomass storage. In the larger containers (0.1m3) there was higher total biomass, longer root length, 62.17cm and the substrate had lower resistance to penetration (0.52Kg cm-2) and temperature. Leaf temperature was directly related to the soil temperature and inversely related to the soil moisture. It was verified that the size of the container affects the physical characteristics of substrate and the plant growth, which suggests that with 0.02m3 pot (of 45cm height) the plants can last more than 180 days at the nursery.